Relinquishing Owners Underestimate Their Dog's Behavioral Problems: Deception or Lack of Knowledge? - Powell, Lauren; Duffy, Deborah L.; Kruger, Katherine A.; Watson, Brittany; Serpell, James A. (Frontiers in Veterinary Science, 2021)
Undesirable behavior is a leading cause of canine relinquishment. Relinquishing owners could provide valuable information about their dog’s behavior, although the reliability of their reports has been questioned by the sheltering community. This study aimed to investigate a) whether relinquishing owners’ reports of dog behavior differed based on the behavioral screening method; b) whether relinquishing owners’ reports were impacted by the confidentiality of their responses; and c) whether relinquishing and non-relinquishing owners perceived the behavior of their dogs differently. The sample included 427 relinquished dogs from 3 animal shelters and 427 pet dogs, matched for sex and breed. Owners responded to a direct question about whether they were experiencing problems with their dog’s behavior and completed the mini C-BARQ which includes 42 questions about the frequency and severity of specific canine behaviors in various circumstances. More than two-thirds (69.3%) of relinquishing owners indicated they were not experiencing problems with their dog’s behavior when asked directly, compared with only 34.5% of pet owners. Yet, relinquished dogs had significantly higher (less desirable) scores than pet dogs across most C-BARQ scales. The disparity between C-BARQ scores and the single, direct question does not appear to be the result of deliberately biased reporting by relinquishing owners as the perceived confidentiality (or lack thereof) did not affect their responses (X2=1.44, p=0.97). It is possible that relinquishing owners had less understanding of dog behavior and did not recognize behavior problems as a problem. Our findings support the use of standardized behavioral questionnaires, such as the mini C-BARQ, to collect behavioral information from owners at the time of relinquishment and highlight opportunities for animal shelters to reduce relinquishment by assisting owners to recognize and manage behavioral problems.